2015
DOI: 10.1096/fj.14-264796
|View full text |Cite
|
Sign up to set email alerts
|

ATP‐binding cassette transporters and sterol O ‐acyltransferases interact at membrane microdomains to modulate sterol uptake and esterification

Abstract: A key component of eukaryotic lipid homeostasis is the esterification of sterols with fatty acids by sterol O-acyltransferases (SOATs). The esterification reactions are allosterically activated by their sterol substrates, the majority of which accumulate at the plasma membrane. We demonstrate that in yeast, sterol transport from the plasma membrane to the site of esterification is associated with the physical interaction of the major SOAT, acylcoenzyme A:cholesterol acyltransferase (ACAT)-related enzyme (Are)2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 55 publications
3
19
0
Order By: Relevance
“…Aus1 and Pdr11 form a complex in the plasma membrane and are together essential for sterol import [27,28,29]. DAN1 is another anaerobic gene whose expression is induced by Upc2 [27,30].…”
Section: Functions Of Ecm22 Upc2 Sut1 and Sut2 In Budding Yeastmentioning
confidence: 99%
“…Aus1 and Pdr11 form a complex in the plasma membrane and are together essential for sterol import [27,28,29]. DAN1 is another anaerobic gene whose expression is induced by Upc2 [27,30].…”
Section: Functions Of Ecm22 Upc2 Sut1 and Sut2 In Budding Yeastmentioning
confidence: 99%
“…The two enzymes are not influenced by the ergosterol concentration itself (no product inhibition). Moreover, studies have shown that an enhanced capacity to esterify sterols, in this case by the overexpression of ARE2 , which is localized directly at sterol‐rich microdomains (Gulati, Balderes, et al, ), can enrich the sterol content in yeast (Polakowski, Bastl, Stahl, & Lang, ). In the study of Rintala et al .…”
Section: Resultsmentioning
confidence: 99%
“…We hypothesize that reduction of the ATPase activity of the importers affects esterification of exogenous sterols and their relocalization to lipid particles. Recent results of Gulati et al (2015) demonstrated tight interaction between sterol import and sterol esterification. Thus, if sterol esterification enzymes (Are2 and Are1) are direct acceptors of the imported sterol from Aus1/Pdr11, their activity can significantly influence efficiency and selectivity of the import.…”
Section: Discussionmentioning
confidence: 99%